To Avoid Pain or Die Trying: A Philosophical interpretation of Epicureanism - Kristen Beard (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
The school of Epicureanism promotes a philosophy based on hedonism, arguing that pleasantness constitutes goodness. Thus the goal of life is to pursue pleasure. For the Epicureans, the highest pleasure is simply the total absence of pain, and nothing more. Mental pains are much more powerful than physical ones, so the best way to maximize pleasure is to abandon mental pains. Traditional interpretation of Epicurean text says that the primary mental pain that burdens human pleasure is fear, especially the fear of death. Further, humans can eliminate their fear completely by evaluating it with rational discourse. I argue, however, against this traditional interpretation. I interpret the Epicurean texts to hold that fear cannot be eliminated completely: based on Epicurean texts, fear results when basic needs such as food, water, and shelter become threatened.